Usefulness of scintigraphy with labelled leucocytes and SPECT/CT in vascular graft infection (2017)
Vascular graft infections are a rare complication in this type of procedure. However, when they do occur, they usually have high morbidity, and even a high mortality. Proper identification and location is crucial for the appropriate and early management, whether medical or surgical, thus knowledge of the right tools is paramount. Nuclear medicine studies play an important role in this regard, either by using labelled white blood cells scintigraphy or 18F-FDG. The choice, among other factors, will depend on the experience with both techniques by the different groups, their knowledge of them, as well as their availability. Two cases are presented in which 99mTc-HMPAO-white blood cells SPECT/CT scintigraphy was very useful in the diagnosis and location of the suspected infectious compromise, which led to the subsequent appropriate and guided management. Both cases were confirmed clinically and microbiologically. © 2017 Elsevier España, S.L.U. y SEMNIM